Case files. - Toy, Eugene C.; Klamen, Debra L. (McGraw Hill Medical, 2012)
Sixty high-yield psychiatry cases help you sharpen your diagnostic and problem-solving skills You need exposure to high-yield cases to excel on the psychiatry clerkship and the shelf-exam. Case Files: Psychiatry presents sixty real-life cases that illustrate essential concepts. Each case includes complete discussion, clinical pearls, references, definitions of key terms, and USMLE-style review questions with detailed explanations of the correct answers. With this system, you'll learn in the context of real patients, rather than merely memorize facts.